2021
DOI: 10.14202/vetworld.2021.1197-1201
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the first intron and exon of the myostatin gene in several Indonesian cattle populations

Abstract: Background and Aim: Myostatin (MSTN), a member of the transforming growth factor-β family, is a negative regulator of muscle mass. This study aimed to detect the genetic variation of the 1160 bp fragment of exon 1 and part of intron 1 of the MSTN gene in several cattle populations raised in Indonesia. Materials and Methods: Polymerase chain reaction products of the MSTN gene amplified from 92 animals representing 10 cattle populations (Peranakan Ongole [PO], Belgian Blue x PO cross, Rambon, PO x Bali cross, J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…A similar occurrence also happened to Madura cattle, which is the result of a crossbreeding between Bali cattle (Bos javanicus) and Ongole cattle (Bos indicus) when people from India came to Indonesia 1500 years ago and had been continuously breeding on the Madura island [19]. [20] that reported three genotypes in the PO cattle population using sequencing techniques: CC, CG, and GG. However, similar results were obtained regarding the genetic diversity of the MSTN gene in Madura cattle, which only showed the CG and GG genotypes.…”
Section: Polymorphism Of the Mstn Genementioning
confidence: 75%
“…A similar occurrence also happened to Madura cattle, which is the result of a crossbreeding between Bali cattle (Bos javanicus) and Ongole cattle (Bos indicus) when people from India came to Indonesia 1500 years ago and had been continuously breeding on the Madura island [19]. [20] that reported three genotypes in the PO cattle population using sequencing techniques: CC, CG, and GG. However, similar results were obtained regarding the genetic diversity of the MSTN gene in Madura cattle, which only showed the CG and GG genotypes.…”
Section: Polymorphism Of the Mstn Genementioning
confidence: 75%
“…Considering the importance of this gene, investigation of the biological roles of the MSTN gene in Ongole cattle is required because mutations in some of the other beef cattle, including European cattle [ 23 , 27 , 28 ], Australian breeds [ 30 ], and Indonesian beef cattle [ 31 , 32 , 35 ] are associated with growth traits. The literature search revealed that there is no prior research examining the allelic and genotypic frequencies of the MSTN gene in SO cattle, making direct comparisons with other studies in Ongole cow breeds worldwide difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the MSTN gene in economic production has been identified in various breeds of beef cattle, such as Belgian blue [ 26 ], Nellore cattle [ 25 , 27 ], Piemontese young bulls [ 23 , 28 ], Russian cattle [ 2 ], Marchigiana bulls [ 3 ], and, Chinese yellow cattle [ 29 ]. The trait can be found in Australian beef cattle [ 30 ] and in some breeds of Indonesian beef cattle, such as the Peranakan Ongole (PO), the Belgian Blue × PO hybrid, and the PO × Pegolo Bali cattle [ 31 , 32 ]. However, the result might probably be different from other Ongole beef cattle extensively grazed under a harsh environment in a tropical semi-arid region, such as Sumba Island [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations